Wait-Free Global Virtual Time Computation in Shared Memory TimeWarp Systems - Pellegrini, Alessandro; Quaglia, Francesco (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2014: Anais do XXVI International Symposium on Computer Architecture and High Performance Computing, 2014)
Global Virtual Time (GVT) is a powerful abstraction used to discriminate what events belong (and what do not belong) to the past history of a parallel/distributed computation. For high performance simulation systems based on the Time Warp synchronization protocol, where concurrent simulation objects are allowed to process their events speculatively and causal consistency is achieved via rollback/recovery techniques, GVT is used to determine which portion of the simulation can be considered as committed. Hence it is the base for actuating memory recovery (e.g. of obsolete logs that were taken in order to support state recoverability) and nonrevocable operations (e.g. I/O). For shared memory implementations of simulation platforms based on the Time Warp protocol, the reference GVT algorithm is the one presented by Fujimoto and Hybinette [1]. However, this algorithm relies on critical sections that make it non-wait-free, and which can hamper scalability. In this article we present a waitfree shared memory GVT algorithm that requires no critical section. Rather, correct coordination across the processes while computing the GVT value is achieved via memory atomic operations, namely compare-and-swap. The price paid by our proposal is an increase in the number of GVT computation phases, as opposed to the single phase required by the proposal in [1]. However, as we show via the results of an experimental study, the wait-free nature of the phases carried out in our GVT algorithm pays-off in reducing the actual cost incurred by the proposal in [1].